2022
DOI: 10.1002/smr.2500
|View full text |Cite
|
Sign up to set email alerts
|

Towards roadmap to implement blockchain in healthcare systems based on a maturity model

Abstract: Healthcare systems face various issues related to complex networks of intermediaries and a lack of transaction traceability. The most critical issues are the fragmentation of healthcare data, obstacles in providing efficient research and services, lack of clinical trial reporting, high cost and mismanagement of the drug supply chain, patient data security, and fake drugs. Blockchain technology has the potential to address these criticalities as it has in build traceability mechanisms and promises new business … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…This integrative review is expected to identify optimal approaches to implementing and evaluating the effectiveness of blockchain-based dynamic consent technologies. While blockchain products are being developed for health research environments, few implementation models exist [ 52 ]. Additionally, few articles describe their products’ limitations or weaknesses, contributing to narrow and unrealistic perspectives [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…This integrative review is expected to identify optimal approaches to implementing and evaluating the effectiveness of blockchain-based dynamic consent technologies. While blockchain products are being developed for health research environments, few implementation models exist [ 52 ]. Additionally, few articles describe their products’ limitations or weaknesses, contributing to narrow and unrealistic perspectives [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our future work includes implementing a GSD project management maturity model and developing the model's maturity levels 52 . We aspire to conduct a case study with GSD organizations to gain insights from practitioners on the structure, ease of use, and understanding of a GSD project management maturity model.…”
Section: Discussionmentioning
confidence: 99%
“…Our future work includes implementing a GSD project management maturity model and developing the model's maturity levels. 52 We aspire to conduct a case study with GSD organizations to gain insights from practitioners on the structure, ease of use, and understanding of a GSD project management maturity model. Improvements could be made by employing methods related to the PRISMA methodology, 53 identifying bigdata sources, current research trends using bibliometric techniques, 54 and exploring other fuzzy theories.…”
Section: Conflict Of Interest Statementmentioning
confidence: 99%
“…According to [36], there are obvious differences in the comprehensive performance of the available BDMMs. After reviewing the previous studies related to maturity models, the results indicated that the models of [45] and [47] provide end-users with all descriptive, prescriptive, and comparative functionalities, while the models of [38,48,50,62] serve a descriptive or prescriptive purpose of use. The models of [49,52] were the only ones acting as descriptive models, not providing any recommendations or improvement activities.…”
Section: The Limitations Of the Available Bdmmsmentioning
confidence: 99%